Combination of IKZF1 deletion and early molecular response show significant roles on prognostic stratification in Philadelphia chromosome-positive acute lymphoblastic leukemia patients. Issue 8 (3rd August 2018) - Li, He; Zhang, Wanhua; Kuang, Pu; Ye, Yuanxin; Yang, Jinjun; Dai, Yang; Lu, Xiaojun; Zheng, Yuhuan; Liu, Ting
Abstract: We retrospectively analyzed the samples collected from 66 patients with Ph + ALL enrolled on ChiCTR-TNRC-09000309 clinical trial. CR rate was 95.5%, and estimated 2-year OS and DFS were 51.7 ± 11.7% and 26.9 ± 11.6%, 3-year OS and DFS were 31.6 ± 12.0% and 23.4 ± 11.6%. By combining IKZF1 deletion and early molecular responses, we redefined the patients as low, intermediate, and high risk 3 groups separately. Patients with double negative in IKZF1 and early molecular response experienced significant superior survival, while patients with double positive would have the worst outcome, and patients who were one or the other with IKZF1 deletion or MRD status had intermediate outcome. Significant differences were found among 3 groups in regard to both OS ( p  < .001) and DFS ( p  < .001). Our findings suggest that Ph + ALL is a heterogeneous group of diseases with significantly different prognosis. Combination of IKZF1 deletion and MRD status enable better risk stratification of patients for assignment to optimal therapeutic strategies.